Threshold values on environmental chemical contaminants in seafood in the European Economic Area. (August 2022) - De Witte, Bavo; Coleman, Bert; Bekaert, Karen; Boitsov, Stepan; Botelho, Maria João; Castro-Jiménez, Javier; Duffy, Conor; Habedank, Friederike; McGovern, Evin; Parmentier, Koen; Tornero, Victoria; Viñas, Lucia; et al.
Abstract: Seafood safety regulation within the European Economic Area has been strongly harmonised, including uniformisation of maximum levels on contaminants and toxins in seafood. Nevertheless, individual countries still have national limit values for different contaminant groups. This publication summarizes currently existing maximum levels on environmental chemical contaminants in seafood and seaweed that are established within the European Economic Area at international or national level. Maximum levels are compared to legal thresholds in other North Atlantic countries that are member of the International Council for the Exploration of the Seas (ICES), i.e. US, Canada and Russia, as well as the international food standards of the Codex Alimentarius. The identification of seafood safety regulatory differences allows to identify current challenges, associated to different topics: (1) contaminants in seafood, (2) contaminants in seaweed and (3) natural aquatic toxins. It can be concluded that increased harmonisation within and between geographical regions e.g. on seaweed regulations, can be beneficial from both a health and economic perspective. Constantly evolving knowledge on contaminants of emerging concern and new or emerging toxins triggers a continuous process of updating seafood regulations. Due to the health benefits of seafood consumption, a balance between risks and benefits is essential, as considered in EFSA seafood consumption advice.